Bond behaviour and thermal stability of flax/glass hybrid fibre reinforced polymer–timber structures connected by polyurethane. (7th March 2022) - Huang, Silu; Bachtiar, Erik Valentine; Yan, Libo; Kasal, Bohumil
Highlights: The bond between FG-PUR and timber was evaluated through single-lap shear tests. The LVL-PUR-GF showed higher average shear strength, strain efficiency and fracture energy than the LVL-PUR-FG. The LVL-PUR-GF had higher strain efficiency and fracture energy than LVL-PUR-GG. The thermal stability of FG-PUR was higher than FF-PUR by incorporating glass fibres. Abstract: In this paper, the bond behaviour between timber and flax-glass hybrid fibre reinforced polyurethane polymer (HFRP) joints was investigated. The HFRP and timber (termed as HFPR-timber) joints were bonded by polyurethane adhesive. The influence of fibre layer sequences of HFRP on the shear strength and fracture energy of HFRP-timber joints was investigated with a single-lap shear test. Based on the tensile test results of FRP and combined with results from the single-lap shear test, the strain efficiency of the HFRP-timber bond was also calculated. In addition, Fourier transformed infrared spectroscopy (FTIR) was performed to analyse the surface chemical reaction between polyurethane adhesive and the flax fibre. Thermogravimetric analysis (TGA) was also conducted to evaluate the thermal stability of the HFRP, timber and their joints. Furthermore, scanning electronic microscopy (SEM) was used to study the microstructure of the HFRP-timber joints. The results showed that the fibre sequence in the HFRP affected the bond behaviour between the HFRP and timber remarkably. The highest shear strength, strain efficiency, and fracture energy were obtained, when the glass fibre layer was placed next to the timber substrate. FTIR and SEM studies showed that the flax and glass fibres in the FRP composites were not fully saturated by the polyurethane. The TGA results showed that the combination of glass and flax fibres in HFRP led to a higher thermal stability in comparison to flax FRP alone.